Patriarchy Without Masculinity in Homa-Bay County of Kenya (1894-2022) - Orondo, John Akumu; Budi, Nashon Budy; Okoth, George Odhiambo; Onjala, Isaya Oduor (Journal of Historical Studies, 2023)
Purpose: The purpose of this treatise is to justify the existence of patriarchy without masculinity because of the existence of patriarchal shell as evidenced in the male failure to meet the societal expectation of a functioning masculinity. This study is premised in the pre-colonial belief that in patriarchal society men made far-reaching decisions, they were the breadwinners and wielded exclusive authority and power. Methodology: The study used historical research design of Gottschalk Louis to collect, verifies, and synthesizes evidence from the past to establish facts that defended the existence of patriarchy without masculinity in Homa Bay. Purposive and snowball sampling techniques were used to identify the individuals and gender groups informants during the primary data collection. Primary data was also gathered from the National Archives to triangulate oral and secondary data. Secondary data were collected from, thesis, journal articles, books, and other publications from the internet, university, and other libraries. Findings: The data collected is given thematic content analysis based on study question. Primary and secondary data sources were corroborated to attain the validity and reliability of findings. The publication utilizes patriarchal theory of Robert Filmer which highlights the role of culture on gender performance roles and explains the role of patriarchal ideology in elevating men and making woman to depend on them for survival. In this study masculinity is viewed as a quality or set of habitual performed roles which were stereotypically connected with male gender as opposed to inherent in male. Contrary to the above, this study established that men still claim to have socio-economic and political entitlement in Homa Bay but the level of degeneration and reduction on the same is below expectation. Such degeneration makes patriarchy a shadow of its original reality. This premised in the study findings that there exists a widening masculine gap between the pre and postcolonial men of Homa Bay. The evidence in Homa Bay shows that most men fail to meet the societal expectation in their performances but grapple with vulnerability as they helplessly stare at the systematic loss of pre-colonial socio-economic and political patriarchal authority. Unique Contribution to Theory, Policy and Practice The existence indicators of the decline of patriarchal dominance in Homa Bay such as long-life expectancy among women, high birth rate among baby girls and the socioeconomic and political degeneration, make patriarchal; theory to be rethought. This paper shows that in the pre-colonial society, there was a concept of valorized hegemonic masculinity which men strived to emulate that consequently established patriarchy. Therefore, the policy makers, governments and the non-governmental organizations should reorganize their strategies to save masculinity from extinction for the purpose of gender egalitarian societies.